Evaluation of chitoligosaccharides effect upon probiotic bacteria - Fernandes, João C.; Eaton, Peter; Franco, Isabel; Ramos, Óscar S.; Sousa, Sérgio; Nascimento, Henrique; Gomes, Ana; Santos-Silva, Alice; Xavier Malcata, F.; Pintado, Manuela E. (International journal of biological macromolecules, 2012)
The main objective of the present study was to evaluate the antibacterial effect – through the determination of minimum inhibitory (and lethal) concentrations, as well as the possible prebiotic potential of chitooligosaccharides (COS) – through the determination of growth curves, on Bifidobacterium animalis Bb12, Bifidobacterium animalis Bo and Lactobacillus acidophilus Ki. Atomic force microscopy was further used to obtain high resolution images of COS effects upon the cell morphology. Our results demonstrate that COS do not stimulate the growth of those strains, neither the strains are capable of using COS as a primary source of carbon. Analysis of morphology when exposed to inhibitory/bactericidal concentrations, suggested that COS do not exert any direct damage upon the bacteria structure, instead the bacteria are apparently covered by COS, which likely prevent nutrient uptake.